Variasi komposisi daun Ketapang dan kulit pisang sebagai media tumbuh pakan alami jentik nyamuk - Tununu, Riky R.; Solang, Jhonly; Pangkey, Henneke; Mingkid, Winda M.; Kreckhoff, Reni L.; Kusen, Diane J.; Wantasen, Adnan (Universitas Sam Ratulangi, 2021)
This study aimed to 1) determine the best combination between ketapang and banana peels for the propagation of life feed mosquito larvae; 2) determine the culture media that can produce mosquito larvae optimally. The containers used in this study were 24 buckets with a size of 5 litres. Some of the materials used in the study were dried ketapang leaves, goroho banana peels, kepok banana peels and water. This study used a factorial Completely Randomized Design (CRD) consisting of two factors and three replications. The first factor was the difference in the number of ketapang leaves. The second factor was the difference in banana peels types. The first factor included the difference in the number of ketapang leaves, consisting of: Treatment 0 = without ketapang leaves, Treatment 1 = 50 grams of ketapang leaves, Treatment 2 = 75 grams of ketapang leaves, Treatment 3 = 100 grams of ketapang leaves. The second factor included differences in banana peels, which consist of: Treatment 1 = one kepok banana peel, Treatment 2 = one goroho banana peel. The results were different types of banana peels affected the numbers of mosquito larvae, where the best was kepok banana peels; the difference in weight of ketapang leaves did not have a significant effect on the number of mosquito larvae. The container used in this study was a bucket with a volume of 5 L. The banana peels used were goroho banana peels and ripe yellow kapok banana peels. Ketapang leaves were preapared with a weight 0f 0, 50, 75, and 100 grams, respectively. Shoe banana peels andÂ goroho banana, one skin eachand ketapang leaves 0, 50, 75, and 100 grams, respectively, put together wit the jalah used to wrap between ketapang leavesand spatu banana peels and goroho banana, then put into a container that has been filled wit 3 L of water.